2007
DOI: 10.3177/jnsv.53.95
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Injury to Rats Fed on Soybean Protein-Based Vitamin B12-Deficient Diet Can Be Reduced by Methionine Supplementation

Abstract: SummaryWe have previously reported that rats fed on a vitamin B 12 (B 12 )-deficient diet containing 180 g soybean protein per kg diet showed marked histologic damage in their testes. In this paper, we report the effect of B 12 -deficiency on B 12 -dependent methionine synthase in the rats' testes and the effect of methionine supplementation of the diet on testicular damage. Rats were fed the soybean protein-based B 12 -deficient diet for 120 d. We confirmed that those rats were in serious B 12 -deficiency by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
13
0
3
Order By: Relevance
“…Furthermore, methionine is one of the amino acid building blocks of protein and acts as the universal methyl group donor ( S ‐adenosylmethionine) for a large number of methylation reactions. Yamada et al [29] reported that reduced testicular MS activity is the primary cause of pathological impairment of spermatogenesis owing to B 12 deficiency and that methionine supplementation to the diet can reduce this impairment. Bennet [30] has reported that B 12 deficiency may lead to recurrent fetal death owing to the elevated Hcy levels.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, methionine is one of the amino acid building blocks of protein and acts as the universal methyl group donor ( S ‐adenosylmethionine) for a large number of methylation reactions. Yamada et al [29] reported that reduced testicular MS activity is the primary cause of pathological impairment of spermatogenesis owing to B 12 deficiency and that methionine supplementation to the diet can reduce this impairment. Bennet [30] has reported that B 12 deficiency may lead to recurrent fetal death owing to the elevated Hcy levels.…”
Section: Resultsmentioning
confidence: 99%
“…In cases of vitamin B 12 deficiency, the metabolic conversion is not performed and homocysteine levels are elevated in the blood [Yamada et al, 2007]. Therefore, to verify if the treatment with cimetidine leads to vitamin B 12 deficiency, plasma concentrations of vitamin B 12 and total homocysteine were evaluated by electrochemiluminescence and chemiluminescence assays, respectively (São Lucas Clinical and Microbiological Laboratory).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Vitamin B 12 stimulates DNA synthesis, contributing to cellular division [Beck et al, 1965;Oh and Brown, 2003]. In the testis, vitamin B 12 has demonstrated to play a role in the maintenance of testicular functions [Hata et al, 2002;Webster et al, 2005;Yamada et al, 2007]. In vitamin B 12 -deficient rodents, testicular pathological disorders have been demonstrated, such as significant reduction of testis weight, atrophy of the seminiferous tubules and aplasia of spermatids and sperm [Kawata et al, 1992[Kawata et al, , 1997[Kawata et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…C and CM group rats received 1 g of cyanocobalamin (Wako Pure Chemicals) per day by oral administration. The composition of experimental diets was previously described [9,11] . At the end of the breeding period, blood was collected from the hearts of rats under anesthesia, and the liver was removed.…”
Section: Animalsmentioning
confidence: 99%